(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The aim of this study is to give general information about all different polymer foam materials with various morphologies, pore sizes and properties. Therefore, firstly, the formation principles and techniques and properties of polymer foams are explained, and then information is given about the physical and chemical foaming agents used in the preparation of polymer foams. Then, an overview of the articles on polymer foam materials is presented.